Perception versus reality: The portfolio allocations of UK property companies - Mohd. Ali, Hishamuddin; Ruddock, Les (2000)
The property portfolio allocation of property companies could be determined through a risk and return analysis of each sector considering an acceptable level of risk. This study applied a constrained multiple regression model to the examination of property portfolio exposure. An asset class factor model namely return-based style analysis (RBSA) was developed by Sharpe (1988, 1992) to measure the exposures of each component of a mutual fund’s portfolio to movements in their returns. Total returns from ten public-listed property companies (PLPCs), based on their share price movements, were used to estimate the style exposures of three commercial property types - retail, office and industrial. The data used for share price movements are from the first quarter of 1987 to the fourth quarter of 1998. The study examined the relationship of the return for three commercial property types to each portfolio of PLPC. The effective portfolio allocations that are derived by RBSA are then compared with the actual average portfolio allocation of the property companies. RBSA is seen to be a particularly effective tool in the explanation of the returns of PLPCs pursuing growth or income strategies. This study also found that other aspects of portfolio allocation determinants such as gearing, the features of the property portfolio and the property market cycle were worthy of consideration.